Front Cover. Issue 12 (27th June 2022) - Unknown
Abstract : Cover illustration Codium fragile. The cover image refers to the article by Seki et al. 'Discovery of a novel siphonaxanthin biosynthetic precursor in Codium fragile that accumulates only by exposure to blue‐green light' (photo credit: Haplochromis from Wikimedia Commons).